PENGARUH BIMBINGAN KELOMPOK DENGAN TUNJUK AJAR MELAYU TERHADAP HUBUNGAN SOSIAL SISWA MTS AL-MARZUQIN PEKANBARU - Safitri, Olly; Saam, Zulfan; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This study aims to determine the description of students' social relationships before and after being given group guidance treatments with tunjuk ajar melayu, knowing the differences in social relations before and after being given treatment group guidance with tunjuk ajar melayu and to fid out the influence of the treatmens of group guidance with tunjuk ajar melayu to relationships social students. This research is a quantitative study with an experimental method, the research design used is pre-experimental with one group pre-test and post-test approach. The subjects in this study were 8 students taken by purposive sampling technique with the criteria for the results of the scale of social relations (questionnaire) . The results showed that: (1) students' social relations before being given group guidance with tunjuk ajar melayu were mostly in the low category and after being given group guidance with tunjuk ajar melayu were mostly in the high and very high category. (2) there is a significant difference in the level of social relations of students before and after being given group guidance with tunjuk ajar melayu. (3) there is a significant influence on students' social relationships before and after being given group guidance with tunjuk ajar melayu .Key Words: Social Relations , Tunjuk Ajar Melayu, Group Guidance